IoT streams for data-driven predictive maintenance and IoT, edge, and mobile for embedded machine learning: Second International Workshop, IoT Streams 2020 and First International Workshop, ITEM 2020, co-located with ECML/PKDD 2020, Ghent, Belgium, September 14-18, 2020 : revised selected papers - Gama, João; Pashami, Sepideh; Bifet, Albert; Sayed-Mouchaweh, Moamar; Fröning, Holger; Pernkopf, Franz; Schiele, Gregor; Blott, Michaela (Communications in Computer and Information Science, 2020)
Stream Learning -- Feature Learning -- Unsupervised Machine Learning -- Hardware -- Methods -- Quantization.